2021
DOI: 10.29408/ab.v2i1.3776
|View full text |Cite
|
Sign up to set email alerts
|

Pendampingan peningkatan profesionalitas guru Bahasa Indonesia melalui literasi menulis artikel di jurnal ilmiah

Abstract: Teachers are currently required to produce scientific works, especially writing scientific articles. The purpose of this community service is to improve teacher professionalism literacy in writing scientific articles. The method applied in community service activities is descriptive qualitative through training and mentoring activities intended for teachers of the Indonesian Language Senior High School Subject Teacher Consultation (MGMP) in Sukoharjo. The implementation method in community service is carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Consistent with the findings of Isa et al (2016), Hutajulu et al (2020 found that the quality of scientific writing in Indonesia is significantly lower than in its immediate neighbors. Educators, including teachers and professors, need to participate in socialization or training to ensure they maintain the expertise crucial to the field of education and, specifically, to the enhancement of the quality of education they provide their students (Wicaksana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with the findings of Isa et al (2016), Hutajulu et al (2020 found that the quality of scientific writing in Indonesia is significantly lower than in its immediate neighbors. Educators, including teachers and professors, need to participate in socialization or training to ensure they maintain the expertise crucial to the field of education and, specifically, to the enhancement of the quality of education they provide their students (Wicaksana et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Tujuannya untuk memotivasi siswa agar lebih berani untuk mengemukakan pendapat, menghargai pendapat sesama teman, dan saling memberi pendapat (Risdiyanto, 2021). Pada awal tiap pertemuan, siswa diminta untuk membaca terlebih dahulu bahan ajar yang telah dipersiapkan, karena membaca merupakan salah satu langkah untuk memperkaya atau memperbanyak kosa kata yang dimiliki (Wicaksana et al, 2021). Pada pertemuan terakhir, di setiap tingkatan diberikan 5 nomor soal untuk mengukur kemampuan akhir.…”
Section: Pelaksanaanunclassified